UNA HISTORIA DE NODIER, LA HISTORIA DE HELENA GILLET - Palacios Bernal, Concepción (Anales de Filología Francesa, 2007)
Practically unknown in Spanish-speaking countries today, throughout the nineteenth century Nodier was one of the best known French writers in Spain. What follows is the first Spanish translation of Histoire de Hélène Gillet, prefaced by an introduction that details the circumstances and characteristics of the text. As in other works, the French writer uses some fixed procedures to present his ideas. Nodier transforms this short story, based on events that happened in the seventeenth-century, in a reaffirmation of his view of fantastic literature and in an appeal against the death penalty.